Oscillation Criteria of Fourth-Order Differential Equations with Delay Terms. (24th August 2022) - Balatta, Shoura Ahmed; Hashim, Ishak; Bataineh, Ahmad Sami; Ismail, Eddie Shahril
Abstract : The aim of this paper is to derive oscillation criteria of the following fourth-order differential equation with delay term r x z ′ ′ ′ x γ ′ + ∑ i = 1 n q i x f z η i x = 0, under the assumption ∫ x 0 ∞ r − 1 / γ s d s = ∞ . The results are based on comparison with the oscillatory behaviour of second-order delay equations and the generalised Riccati transformation. Not only do the provided theorems provide an entirely new technique but also they vastly improve on a number of previously published conclusions. We give three examples to illustrate our findings.